Mempertanyakan Eksistensi Profesi Akuntan Dalam Industri 4.0: Pendekatan Scoping Review - Yasmi Nurdin; Dian Novita; Muhammad Irdam Ferdiansah (Jurnal Akuntansi dan Pajak, 2023)
The industrial revolution 4.0 illustrates that all work will be replaced by robots or machines that have artificial intelligence (AI) systems. Now, some human jobs have indeed been replaced by computers and machines. The accounting revolution 4.0 is a new concept that leads to a massive change in the world of accountants. There are three things that need to be considered in the accounting revolution 4.0 to be compatible with the industrial revolution 4.0. The first is a change in accounting processes and systems to support the conditions faced in the future industrial world. Shifting the old paradigm regarding the science and function of accounting is the basis for creating a new paradigm for the science and function of accounting in the future. A new paradigm that requires the involvement of technology in every process and at the same time strengthening the character of accountants will be the main weapon. This new paradigm will shape a different business atmosphere, especially from an accounting point of view. The second stage is the implementation of a new paradigm for accounting professionals. At this point, increasing the standardization and competence of accountants is very important to do. The capability of a professional accountant is now not only a technical worker and bookkeeper but has increased to the stage of strategic decision-making by utilizing the latest technology.